2001
DOI: 10.1002/1097-0010(200102)81:3<329::aid-jsfa815>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of a novel raw starch‐digesting amylase from Aspergillus carbonarius

Abstract: A medium was developed to obtain the maximum yield of raw starch-digesting amylase from Aspergillus carbonarius (Bainier) Thom IMI 366159 in submerged culture with raw starch as the sole carbon source. The amylase was puri®ed to apparent homogeneity by sucrose concentration and ion exchange chromatography on S-and Q-Sepharose (fast¯ow) columns. SDS-PAGE revealed two migrating protein bands corresponding to relative molecular masses of 31.6 and 32 KDa. The enzyme was optimally active at pH 6.0±7.0 and 40°C, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 0 publications
4
23
0
Order By: Relevance
“…The activity of the enzyme reported in this study was maximum at 40 o C in agreement with earlier observations for other fungal starch digesting amylases 3,11,12 .Most raw starch digesting amylases are known to exhibit temperature optima between 40 o C and 60 o C and are remarkably stable against high temperatures 13 . Further studies should be carried out to study the stability of the crude enzyme identified in this study in different buffers, so that the temperature optimum may be further enhanced to make use of this enzyme for industrial uses at higher temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…The activity of the enzyme reported in this study was maximum at 40 o C in agreement with earlier observations for other fungal starch digesting amylases 3,11,12 .Most raw starch digesting amylases are known to exhibit temperature optima between 40 o C and 60 o C and are remarkably stable against high temperatures 13 . Further studies should be carried out to study the stability of the crude enzyme identified in this study in different buffers, so that the temperature optimum may be further enhanced to make use of this enzyme for industrial uses at higher temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…Optimal amylase activity was recorded at pH 6.5-8.5, though enzyme was active at lower pH. This was a rare occurrence, most fungal amylase have been reported to be optimally active at the pH range of 4.5 -6.0 (Okolo et al, 2001). The result does not correspond with the optimal pH of 3.0 -5.0 reported for the glucoamylase from Fusarium solani (Bhatti et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
“…Fungal enzymes are more preferable to enzymes from other microorganisms because of their Generally Regarded as Safe (GRAS) status (Sindhu et al, 2009). Studies on fungal amylase especially in the developing countries have concentrated mainly on Aspergillus species probably because of ubiquitous nature and non-fastidious nutritional requirement of this organism (Abu et al, 2005;Gomes et al, 2005;Okolo et al, 2000).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 307-325mentioning
confidence: 99%